2000
DOI: 10.3133/wri004135
|View full text |Cite
|
Sign up to set email alerts
|

Methods for estimating low-flow statistics for Massachusetts streams

Abstract: Methods and computer software are described in this report for determining flowduration, low-flow frequency statistics, and August median flows. These low-flow statistics can be estimated for unregulated streams in Massachusetts using different methods depending on whether the location of interest is at a streamgaging station, a low-flow partial-record station, or an ungaged site where no data are available. Lowflow statistics for streamgaging stations can be estimated using standard U.S. Geological Survey met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Other studies have examined DARs to verify the range for which the DAR method offers estimates of low-flow statistics that are higher quality than estimates determined using regional regression equations (Eash and Barnes, 2017). Koltun and Schwartz (1987) recommended a DAR range from 0.85 to 1.15 for estimating low-flow statistics in Ohio, whereas Ries and Friesz (2000) concluded that a range from 0.3 to 1.5 was appropriate for low-flow statistics in Massachusetts (Eash and Barnes, 2017). The studies mentioned previously recommend using regression equations for ungaged locations outside of their published DAR ranges.…”
Section: Drainage-area Ratio Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have examined DARs to verify the range for which the DAR method offers estimates of low-flow statistics that are higher quality than estimates determined using regional regression equations (Eash and Barnes, 2017). Koltun and Schwartz (1987) recommended a DAR range from 0.85 to 1.15 for estimating low-flow statistics in Ohio, whereas Ries and Friesz (2000) concluded that a range from 0.3 to 1.5 was appropriate for low-flow statistics in Massachusetts (Eash and Barnes, 2017). The studies mentioned previously recommend using regression equations for ungaged locations outside of their published DAR ranges.…”
Section: Drainage-area Ratio Methodsmentioning
confidence: 99%
“…Several studies have reported that the DAR is ideal when the ratio is between 0.5 and 1.5 (Ries and Friesz, 2000). Many of the studies that published this guideline did not offer any scientific basis for how it was set (Ries and Friesz, 2000). This analysis concludes the DAR method or regional regression equations can be used to estimate flow statistics in Kansas based on the results of the Wilcoxon signed-rank test.…”
Section: Comparison To Regression Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic manual streamflow measurements at partial-record streamgages were used concurrently with continuous-record measurements from streamgages in nearby hydrologically similar drainage areas to estimate a continuous daily record at the partial-record streamgages. Specifically, daily streamflow records for the 13 partial-record sites in the Scituate Reservoir drainage area (table 1) were estimated by using the Maintenance of Variance Extension type 1 (MOVE.1) method, as described by Ries and Friesz (2000) and Smith (2015b); data needed to estimate streamflows at partial-record sites were retrieved from the USGS National Water Information System (NWIS; U.S. Geological Survey, 2018). The upper and lower 90-percent confidence limits for the estimated mean annual streamflows, as described by Tasker and Driver (1988), are listed in table 2.…”
Section: Streamflow Data Collection and Estimationmentioning
confidence: 99%